EARNING MANAGEMENT FROM THE PERSPECTIVE OF INSAN KAMIL - Andarsari, Pipit Rosita (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
This article aims to analyze earnings management actions from the perspective of Insan Kamil, characterized as an ideal and perfect human figure. In the portrayal of Insan Kamil, there exist strength, insight, deeds, and wisdom. The interpretative method is employed to analyze earnings management actions ontologically, epistemologically, and axiologically. From an ontological standpoint, earnings management is regarded as a science that can be observed and measured based on empirical evidence. In the epistemological context, Insan Kamil is considered to have a profound understanding of ethical and moral values, such as honesty, integrity, transparency, and adherence to professional ethical standards. Earnings management practices involving manipulation or concealment of information are viewed as violations of these values. Axiologically, earnings management actions may be considered as a potential failure to align rationality with moral values, unless such practices do not violate principles of morality and ethics.